PENERAPAN GAYA KEPEMIMPINAN SITUASIONAL KEPALA SEKOLAH SD NEGERI BALEREJO - Destiyani, Gati; Dwikurnaningsih, Yari; Sugiarto, Agus (Consilium: Education and Counseling Journal, 2025)
The focus of this research is on the situational leadership style of the principal of SDN Balerejo. The aim of this research is to determine the situational leadership style using telling, selling, participating, delegating styles. This research uses a qualitative approach, namely field research. This research uses the following data collection methods: (1) observation, (2) interviews, and (3) documentation. The research location was at SDN Balerejo, and the population was not only teachers and staff but also the principal. The technique used to determine the sample is purposive sampling, namely using snowball sampling to collect data based on weighing results. From the results of the analysis carried out by researchers, the style used by the school principal applies the situational leadership style of telling, selling, participating, delegating, however, selling indicators are dominantly applied by the school principal.